Community involvement in health care in Ghana: an evaluation of Brong Ahafo Rural Integrated Development Programme - Barided (1974-81) - Oppon-Kumi, Augustine (2012)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Science in Regional Planning,